Vertical Readings in Dante's Comedy. Volume 1 - Heather Webb
Vertical Readings in Dante's 'Comedy' is a reappraisal of the poem by an international team of thirty-four scholars. Each vertical reading analyses three same-numbered cantos from the three canticles: Inferno i, Purgatorio i and Paradiso i; Inferno ii, Purgatorio ii and Paradiso ii; etc. Although scholars have suggested before that there are correspondences between same-numbered cantos that beg to be explored, this is the first time that the approach has been pursued in a systematic fashion across the poem. This collection - to be issued in three volumes - offers an unprecedented repertoire of vertical readings for the whole poem. As the first volume exemplifies, vertical reading not only articulates unexamined connections between the three canticles but also unlocks engaging new ways to enter into core concerns of the poem. The three volumes thereby provide an indispensable resource for scholars, students and enthusiasts of Dante.